2021
DOI: 10.1108/jes-01-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the wage differential between the formal and informal economy: a gender perspective

Abstract: PurposeDespite a widespread assertion that wages are lower in the informal than formal economy, there have been few empirical evaluations of whether this is the case and even fewer studies of the gender variations in wage rates in the formal and informal economies. Consequently, whether there are wage benefits to formal employment for men and women is unknown. The aim of this paper is to evaluate the wage differential between formal and informal employment for men and women.Design/methodology/approachTo evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(71 reference statements)
0
0
0
Order By: Relevance
“…Informal employment is associated with a reduced income level and a higher poverty prevalence, as indicated by the (OECD/ILO, 2019). Multiple empirical studies have consistently shown that informal workers earn less than formal workers (Bargain & Kwenda, 2014;Baskaya & Hulagu, 2011;Nordman et al, 2016;Tansel & Acar, 2016;Williams & Gashi, 2022). Therefore, following Engel's law, households with lower incomes devote a more significant percentage of their income to food expenses.…”
Section: Informal Employment and Intra-household Resource Allocationmentioning
confidence: 99%
“…Informal employment is associated with a reduced income level and a higher poverty prevalence, as indicated by the (OECD/ILO, 2019). Multiple empirical studies have consistently shown that informal workers earn less than formal workers (Bargain & Kwenda, 2014;Baskaya & Hulagu, 2011;Nordman et al, 2016;Tansel & Acar, 2016;Williams & Gashi, 2022). Therefore, following Engel's law, households with lower incomes devote a more significant percentage of their income to food expenses.…”
Section: Informal Employment and Intra-household Resource Allocationmentioning
confidence: 99%